Territorial Governance and Competencies of Managing the Territory in the Moroccan Primary Education Curriculum - AOUIDATE, Rachida Allal; AAFIR, Mustapha; Boubria, AbdElouahed (Journal of Educational and Psychological Sciences, 2023)
The aim of this study was to determine the extent to which the Moroccan educational institution is able to build competencies related to territorial management and conservation values among learners, especially in the elementary stage, which is a crucial phase in the formation of learners' personalities as future effective managers of their fields. The study also addressed how to deal with these competencies and local values in terms of theory, through their implementation in curricula and programs of study, as well as in practice, by implementing them by direct educational actors. The study used the descriptive-analytical and historical-evolutionary methods to analyze the data, and it found that the competencies related to territorial management in official guidelines, curricula, and programs of study are not clear and lack the necessary precision. Elementary school graduates are not able to locate themselves within their living environment or understand the components of the soil they live on in a scientific and accurate way, nor are they involved in managing the space of their institution. The study concluded that the Moroccan school, with all its components, including curricula, programs of study, and educational actors, is not able to activate its role in empowering learners with competencies related to territorial management and in forming a generation capable of managing their field wisely and effectively.
Keywords: Territorial Governance; Educational Governance; Empowerment; Competencies; Territorial Management